Asian rural society : - Fukutake, Tadashi (University of Tokyo press, 1967)
This is a collection of the author's essays and survey reports on contemporary Japan, from a sociological point of view. With rich and valuable data, the author presents careful studies of he democratization of the postwar raral community and discusses such imporrant problems for contemporary society as the influence of rapid industrialization on the regional community.